2007
DOI: 10.2320/matertrans.mj200737
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Fragility of Metallic Glass Forming Liquids

Abstract: An expression for the temperature dependence of the viscosity and fragility is derived based on a simple model of the melt. According to the model, the fragility is determined by the relaxation of structural units that form the melt, and is described in terms of the bond strength, coordination number, and their fluctuations of the structural units. It is shown that the fragility of some metallic glass forming liquids such as Pd 40 Ni 40 P 20 , La 55 Al 25 Ni 20 and Zr 65 Al 10 Ni 10 Cu 15 are quite well reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…3. For the sake of comparison, the values of other systems determined previously are also shown [7,8,15]. We can see clearly that strong systems are characterized by large bond strength C and small fluctuations B, whereas fragile systems are characterized by small bond strength and large fluctuations.…”
Section: Application To Ion-conducting Glass-forming Liquidsmentioning
confidence: 94%
See 1 more Smart Citation
“…3. For the sake of comparison, the values of other systems determined previously are also shown [7,8,15]. We can see clearly that strong systems are characterized by large bond strength C and small fluctuations B, whereas fragile systems are characterized by small bond strength and large fluctuations.…”
Section: Application To Ion-conducting Glass-forming Liquidsmentioning
confidence: 94%
“…On the other hand, fragile system such as ZBLA (ZrF 4 -BaF 2 -LaF 3 -AlF 3 ) has a small value of C and a large value of B. Metallic and semiconducting chalcogenide systems exhibit intermediate behavior [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…For instance, it has been shown previously that large value of C and small value of B correspond to strong systems, whereas small value of C and large value of B correspond to fragile systems [11]. From Fig.…”
Section: The Williams-landel-ferry Equationmentioning
confidence: 68%
“…3, we can learn that a high value of the total bond strength between the structural units C and a low value of its fluctuation B results in a less fragile system [11]. The Vogel-Fulcher-Tamman equation…”
Section: The Bond Strength-coordination Number Fluctuation Modelmentioning
confidence: 99%
“…Therefore, it is expected that by using the BSCNF model, further insights on the viscous flow can be extracted which have not been revealed in the analysis by the VFT equation. On this regard, we have already shown that, a quantity N B , which is defined from the BSCNF model [14], gives the number of structural units involved in the thermally activated viscous flow. It has been also shown that N B can be expressed analytically with the BSCNF model parameters [15], and is closely related with the well-known concept of ''cooperatively rearranging region (CRR)'' in the theory of Adam and Gibbs [16].…”
Section: Introductionmentioning
confidence: 99%